2017
DOI: 10.1111/2041-210x.12926
|View full text |Cite
|
Sign up to set email alerts
|

Predicting animal behaviour using deep learning: GPS data alone accurately predict diving in seabirds

Abstract: Abstract1. To prevent further global declines in biodiversity, identifying and understanding key habitats is crucial for successful conservation strategies. For example, globally, seabird populations are under threat and animal movement data can identify key at-sea areas and provide valuable information on the state of marine ecosystems. To date, in order to locate these areas, studies have used global positioning system (GPS) to record position and are sometimes combined with time-depth recorder (TDR) devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 50 publications
(94 reference statements)
3
95
1
Order By: Relevance
“…Movement patterns provide a finer-scale understanding of how animals perceive their habitat (Browning et al, 2018). Movement patterns provide a finer-scale understanding of how animals perceive their habitat (Browning et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Movement patterns provide a finer-scale understanding of how animals perceive their habitat (Browning et al, 2018). Movement patterns provide a finer-scale understanding of how animals perceive their habitat (Browning et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Management of animals threatened by habitat fragmentation often attempt to preserve or restore habitat by planting native vegetation, with the assumption that the resultant structure is suitable for the animals. Effective restoration therefore requires fine-scaled understanding of how animals respond to details of habitat (Allen & Singh, 2016;Browning et al, 2018;McClintock, London, Cameron, & Boveng, 2017). Effective restoration therefore requires fine-scaled understanding of how animals respond to details of habitat (Allen & Singh, 2016;Browning et al, 2018;McClintock, London, Cameron, & Boveng, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, VOD positioning error is probably comparable to what is generally accepted for GPS data, which is estimated to be in the range of 3-28 m (Frair et al 2010). However, while spatial error in tagging technology can lead to the misrepresentation of behaviors in a scale-dependent manner (Costa et al 2010;Browning et al 2017), animal locations can be coded according to behavior (as well as species, age and other factors that may be of interest) with the VOD. The downside of the VOD is that it has relatively intensive requirements when it comes to survey effort.…”
Section: System Performancementioning
confidence: 99%
“…First, some methods assume specific movement properties and/or constraints regarding animal behavior between the observation records. These mechanistic models should include realistic movement properties and certain parametric assumptions (Royer and Lutcavage 2008), which depend on species and environmental conditions (Humphries et al 2010, de Jager et al 2011, Browning et al 2018. Other frequently assumed animal movement behaviors are that animals moving in fluid (i.e., water and air) follow curvilinear rather than linear paths due to flows, vortices, and turbulence (Tremblay et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A recent network analysis has shown that trajectories have a higher predictability than expected; the location of a person can be predicted with 93% accuracy (Song et al 2010), indicating that machine learning, which infers knowledge from trajectory data, is a promising approach to the prediction of animal movements. The use of machine learning has become more common in ecological, behavioral, and environmental research over the last decade (Guilford et al 2009, Resheff et al 2014, Appelhans et al 2015, Valletta et al 2017, Weinstein 2017, Browning et al 2018), but reinforcement learning (RL; Fig. 3; Kaelbling et al 1996, Sutton andBarto 1998), which is a major machine learning paradigm along with supervised and unsupervised learning, has not been applied to animal behavioral data in the field to date.…”
Section: Introductionmentioning
confidence: 99%